Intralocus sexual conflict can resolve the male-female health-survival paradox. Issue 1 (December 2018) - Archer, C.; Recker, Mario; Duffy, Eoin; Hosken, David
Abstract At any given age, men are more likely to die than women, but women have poorer health at older ages. This is referred to as the "male-female, health-survival paradox", which is not fully understood. Here, we provide a general solution to the paradox that relies on intralocus sexual conflict, where alleles segregating in the population have late-acting positive effects on male fitness, but negative effects on female health. Using an evolutionary modelling framework, we show that male-benefit, female-detriment alleles can spread if they are expressed after female reproduction stops. We provide support for our conflict based solution using experimentalDrosophila data. Our results show that selecting for increased late-life male reproductive effort can increase male fitness but have a detrimental effect on female fitness. Furthermore, we show that late-life male fertility is negatively genetically correlated with female health. Our study suggests that intralocus sexual conflict could resolve the health-survival paradox. Although men have lower survival across ages, women have poorer health than men as they age. Here, Archer et al. suggest that this pattern is explained by intralocus sexual conflict and provide supporting evidence from a mathematical model and experiments withDrosophila .